Potential of Bauxite Refining Residue (BR) as CEM II Replacement to Produce Low Carbon Cement - Pavia, Sara (Springer, 2026)
Europe's largest alumina refinery is located in Ireland, with an annual output of approximately 1,900 kilotons. Despite their high efficiency and advanced residue management facilities, they generate significant residue: approximately one tonne of residue per tonne of alumina. This creates a considerable waste management challenge. This study uses Irish bauxite refining residue (BR) in combination with CEM II and ground granulated blast-furnace slag (GGBS) to produce cements with a lower carbon footprint than clinker cements. The Irish BR is characterized by a high iron content and relatively low aluminium and silicon contents which influence the resulting cement performance. Replacing CEM II with BR led to a significant reduction in mechanical strength and flowability. A 20% replacement of CEM II with BR resulted in an 18.33% decrease in compressive strength, while replacements of 40% and 60% caused strength losses of 26.46% and 54.6%, respectively. In contrast, BR demonstrated a good synergy with GGBS. The BR´s high alkalinity served as an activator for the GGBS, promoting gel formation and enhancing mechanical strength development. A combination of 20% BR and 20% GGBS produced mortar with mechanical strength comparable to 100% CEM II mortar. However, the incorporation of BR did not significantly affect the hydration products. Due to the crystalline nature of the BR, inert phases, such as hematite, remained largely unchanged within the hydrated cement matrix.
Construction, Energy, Environment and Sustainability. ICCEES 2025
PUBLISHED
Bari
Keywords: Bauxite refining residue; Portland cement; Clinker cement; Low- carbon cement; reactive waste; circular economy